Peran Dikmas Lantas Unit Dikyasa Satlantas Polres Purwakarta Dalam Menekan Angka Pelanggaran Lalu Lintas Oleh Pelajar SMA/SMK Di Wilayah Hukum Polres Purwakarta - Jonathan Reinhart Pakpahan (Police Studies Review, 2020)
In modern times the hopes / desires of the people namely the creation of traffic order and safety, and to realize this, synergy between the community and the National Police is needed. One of the National Police activities that is preventive in the traffic function is traffic education activities. This study aims to describe the implementation of traffic education activities in order to reduce the number of traffic violations in Purwakarta Police Station, dig deeper into the role of unit members in the Satlantas Purwakarta Police Traffic Unit and find out the factors that influence the Dikyasa unit in carrying out tasks to reduce the number violations of high school / vocational student traffic in Purwakarta district. This research is a descriptive qualitative analysis with field research methods. The focus of the research is the efforts made by the Purwakarta Police Traffic Unit in raising awareness of traffic discipline among high school / vocational high school students. Research data sources consist of primary, secondary and tertiary data. Data collection techniques using observations, interviews and document review. The validity of the data uses triangulation techniques. The data analysis process consists of data reduction, data presentation and drawing conclusions and verification. Based on the research that has been done, the results show that traffic education activities have less effect on reducing the number of Traffic violations in Purwakarta. Factors that influence the implementation of the Dikmas Lantas are inadequate number of Dikyasa Unit members, the function of the traffic education activities is not focused on one target, the material delivered is still in general and the condition of the community who have not responded to the rules. In carrying out the traffic education role, the Dikyasa Unit has carried out collaborations and made supporting programs. Then in the the traffic education activities communication process, it will require additional personnel and quality improvement of human resources by following specialization course, materials tailored to the needs of the community, media adapted to communicants, communicants are prioritized for high school students / Vocational Schools, as well as the effects / impacts arising from the traffic education activities are based on the objectives of Law No.22 of 2009 concerning Road Traffic and Transportation.